2020
DOI: 10.1038/s41598-020-69133-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical evidence of rare porphyrins in purple shells of Crassostrea gigas oyster

Abstract: The colour of oyster shells is a very diverse characteristic morphotype, forming intriguing vivid patterns both on the inside and outside of the shell. In the present study, we have identified for the first time, the presence of several porphyrins as constituents of the shell pigmentation of the Crassostrea gigas oyster consumed worldwide. The precise molecular structures of halochromic, fluorescent and acid-soluble porphyrins, such as uroporphyrin and turacin, are unambiguously determined by reverse phase liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Among the six major signals observed on the chromatogram at 405 nm, the UV-vis absorption pro le of the compound eluted at 30.08 min is characteristic of uroporphyrin I or III on the basis of its Soret and Q bands (Fig. 1) 7 . The major compounds eluted from 12 to 23 min have a broad absorption band from approximately 430 to 600 nm, with λ max ranging from 530 to 486 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the six major signals observed on the chromatogram at 405 nm, the UV-vis absorption pro le of the compound eluted at 30.08 min is characteristic of uroporphyrin I or III on the basis of its Soret and Q bands (Fig. 1) 7 . The major compounds eluted from 12 to 23 min have a broad absorption band from approximately 430 to 600 nm, with λ max ranging from 530 to 486 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the black colour of the adductor muscle scar of shells of the edible oyster Crassostrea gigas, initially hypothesized as a contribution of melanins by S. Hao et al 6 , was subsequently ruled out without resolving the nature of this colour. We also recently identi ed uroporphyrin and derivatives in the mantle of C. gigas and the purple and dark patterns of its shell 7 . These porphyrins, considered as side-products of the highly conserved haem biosynthetic pathway, constitute an evidence of the haem-based cellular respiration of C. gigas 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria-feeding RNAi method used in this study revealed the function of genes related to uroporphyrin pigmentation in C. gigas . The effect of porphyrin pigments on shell color has been reported in mollusks, and uroporphyrin I and III in oyster shells have also been identified [ 3 , 17 , 18 ]. Genes associated with the uroporphyrinogen synthesis have been characterized in marine snails and pacific oysters [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Porphyrins are a widespread group of pigments in nature which are believed to contribute to shell colors in mollusks [ 14 ], often leading to red, brown or purple shell pigmentation [ 3 ]. Among porphyrins, the uroporphyrin I and III are found in mollusks [ 15 , 16 , 17 , 18 ]. It has been suggested that porphyrin in shell pigmentation is produced de novo by the animal through the haem pathway, the production of uroporphyrin is derived from the oxidation of uroporphyrinogen I and III which belong to non-enzymatic side paths [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation